GREEN ECONOMY AND ENVIRONMENTALLY FRIENDLY PROJECTS - Buriyeva, Yulduz Uktamovna (THE INNOVATION ECONOMY, 2026)
This article examines the concept of the green economy, its core principles, and the importance of environmentally friendly projects. Particular attention is paid to the development of the green economy in the Republic of Uzbekistan, including projects related to renewable energy sources, energy efficiency improvement, sustainable transportation, and waste management. The study analyzes the role of these initiatives in promoting socio-economic development, improving public well-being, and maintaining environmental balance. The results show that the transition to a green economy is a key factor in ensuring sustainable development in Uzbekistan.